CURRENT ISSUES IN THE TRAINING SYSTEM OF THE MASTER OF BUSINESS DEVELOPMENT PROGRAMME IN THE LIGHT OF THE FEEDBACK OF THE PROGRAMME LEADERS - Vizdák, Károly; Popovics Ph.D., Péter András (Applied Studies in Agribusiness and Commerce, 2025)
Over the past decades, business schools' Masters in Entrepreneurship Development have become one of the most important venues for training future entrepreneurs worldwide. The concept of entrepreneurship and the role of the entrepreneur has been in a constant state of flux over the years, with a significant impact on the structure, methodology and objectives of training courses. Universities need to focus not only on providing traditional business skills but also on developing competences adapted to an increasingly changing economic and social environment.In this article, after reviewing the most important foreign and domestic literature on the topic, we examine the current situation of Master's programmes in business development in Hungary through qualitative research. We focus on the social and economic changes that have influenced the development of entrepreneurship education in recent years and on the trends that may shape the content and form of education in the coming period. The research will use in-depth interviews with programme leaders to find out what expectations different stakeholders - labour market actors, university leaders, students and external stakeholders - have of the Master's in Business Development. We will explore the entrepreneurial competences and effective educator roles that are seen as key today, as well as the main challenges that programme leaders of training courses are currently facing. Based on this, this paper aims to identify potential opportunities and directions for improvement in the teaching of Masters in Business Development, which can contribute to preparing students more effectively for the challenges of a dynamically changing economic environment.